2021
DOI: 10.2139/ssrn.3851848
|View full text |Cite
|
Sign up to set email alerts
|

Making Entrepreneurs: Returns to Training Youth in Hard Versus Soft Business Skills

Abstract: We study the medium-term impacts of the Skills for Effective Entrepreneurship Development (SEED) program, an innovative in-residence 3-week mini-MBA program for high school students modeled after western business school curricula and adapted to the Ugandan context. The program featured two separate treatments: the hard-skills MBA features a mix of approximately 75% hard skills and 25% soft skills; the soft skills curriculum has the reverse mix. Using data on 4400 youth from a nationally representative sample i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Regular curriculum updates and incorporation of emerging technologies, as recommended by Penprase (2018), are becoming increasingly common. Several studies have confirmed the high demand for soft skills among employers in Uganda, as well as their positive impact on productivity and innovation (Chioda et al, 2021;Gathani et al, 2019;Nampewo et al, 2018). The impact of strong soft skills extends beyond mere employment.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Regular curriculum updates and incorporation of emerging technologies, as recommended by Penprase (2018), are becoming increasingly common. Several studies have confirmed the high demand for soft skills among employers in Uganda, as well as their positive impact on productivity and innovation (Chioda et al, 2021;Gathani et al, 2019;Nampewo et al, 2018). The impact of strong soft skills extends beyond mere employment.…”
Section: Literature Reviewmentioning
confidence: 93%
“…20 Chioda and Carney (2021) show that certain socioemotional skills (i.e., negotiation, persuasion and self-efficacy) led to higher business earnings than hard skills in an impact evaluation of a business skills program in Uganda.…”
Section: Ilo Working Paper 89mentioning
confidence: 98%
“…Finally, an emerging body of evidence (Adhvaryu and Nyshadham, forthcoming;Dimitriadis and Koning, 2022;Chioda and Carney, 2021) highlights the importance of skills for labour market outcomes in LMIC and identifies the relationship of various types of skills and transitions to better jobs as avenues for future empirical research (Bennett et al, 2022;Deming, 2022). We thus investigate the possible relationship between transitioning and skills by including cognitive skills measures in our main estimation.…”
Section: Ilo Working Paper 89mentioning
confidence: 99%